The Influence of Management Commitment and Information Technology Capabilities on Sustainable Value Creation (Survey on Sharia in Jakarta) - BADAWI, Ahmad; NUGROHO, Lucky; HIDAYAH, Nurul (International Journal of Environmental, Sustainability, and Social Science, 2024)
Sharia banks as sharia financial institutions have a role as intermediary institutions to carry out transactions with the community in accordance with the concept of maqasid sharia, namely the purpose of establishing sharia banks is to protect religion, protect the soul, protect the mind, protect descendants, and protect the environment (1) Sharia banking is expected to become a leading banking industry in providing financial services that contribute to the achievement of the Sustainable Development Goals (SDGs), namely the Sustainable Development Goals (SDGs) are development that maintains a sustainable increase in the economic welfare of society, development that maintains the sustainability of life social community, and implementing the principle of Creating Shared Value (CSV) which is actually the basic essence of implementing maqashid sharia in the sharia economy (OJK, 2020). This research is very important for the development of sharia banking in Indonesia which is currently facing competition with conventional banking. The purpose of this research is to analyze the influence of Management Commitment, IT Capability on Sustainability Value Creation. Quantitative research method using PLS analysis tools. The data used is primary data (Questionnaire) with employee respondents at sharia banks in DKI Jakarta. The research results concluded that Information Technology Capabilities and Management Commitment were proven to influence Sustainable Value Creation.